2019
DOI: 10.1159/000496118
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Social Neighbourhood Factors in the Association between Features of the Physical Neighbourhood Environment and Weight Status

Abstract: Background: This paper investigated the independent and joint associations between aspects of the physical neighbourhood environment and social neighbourhood factors with BMI and overweight status in European adults. Methods: Data from 5,199 participants in the SPOTLIGHT survey were analysed. Participants reported on their height, weight and perceptions of the neighbourhood. Objectively measured aspects of the physical neighbourhood environment included: presence of recreational facilities, features of the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
5
1
Order By: Relevance
“… 79 , 80 Given the positive impact of physical activity on children’s BMI, future research could explore whether the use of physical activity facilities is associated with overweight. Additionally, it has been suggested that participation in neighborhood initiatives could be important motivations to change health behavior, such as exercising more outdoors, 20 , 81 but we could not demonstrate that. Similar to the present study, Hoenink et al when evaluating 5199 adults from 5 European countries found no significant associations between overweight and availability of recreational facilities such as gyms, swimming pools, and sports clubs.…”
Section: Discussioncontrasting
confidence: 77%
“… 79 , 80 Given the positive impact of physical activity on children’s BMI, future research could explore whether the use of physical activity facilities is associated with overweight. Additionally, it has been suggested that participation in neighborhood initiatives could be important motivations to change health behavior, such as exercising more outdoors, 20 , 81 but we could not demonstrate that. Similar to the present study, Hoenink et al when evaluating 5199 adults from 5 European countries found no significant associations between overweight and availability of recreational facilities such as gyms, swimming pools, and sports clubs.…”
Section: Discussioncontrasting
confidence: 77%
“…Similarly, some studies found no strong moderation effect of perceived crime and supermarkets on the association between environment and T2DM and body weight. 38 39 Others also found no strong association for area safety that also included violence 40 and objective crime 41 in relation to T2DM and BMI. Nevertheless, those who reported having footpaths and recreational facilities but reported unsafe crime seemingly had a higher T2DM odds.…”
Section: Discussionmentioning
confidence: 99%
“…The deprivation index data used were focused particularly on census data from 2011 (the most recently available during the recruitment process). The deprivation index range included being extremely disadvantaged (1), very disadvantaged (2), disadvantaged (3), marginally below average (4), marginally above average ( 5), affluent (6), very affluent (7), and extremely affluent (8). Due to the final sample size and in order to facilitate statistical analysis, the areas were then re-coded by collapsing responses 1-3 = high deprived; 4-5 = medium deprived; and 6-8 = low deprived.…”
Section: Neighborhood Deprivation Indexmentioning
confidence: 99%
“…For children, the neighborhood environment includes the food outlet(s) where their families purchase food, the streets and roadways on which they travel, the parks and playgrounds in which they spend leisure time, and the other children and adults with whom they interact [6]. Therefore, parent interactions with other residents, as well as the characteristics of a neighborhood, can influence perceptions of the neighborhood environment, both positively and negatively [7]. These perceptions are linked with psychosocial variables such as social support, social cohesion, and trust, as well as with other neighborhood factors such as a sense of safety (e.g., crime and traffic) and socioeconomic status [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation